"Arrasta pra cima": o Jornal Estadão como informação nas interfaces do Instagram e do TikTok - Oliveira, Eduarda Bitencourt de (Universidade do Vale do Rio dos Sinos, 2021)
The following research seeks to understand the information within Estado de S. Paulo Journal on Instagram’s (Stories and Reels) and TikTok’s interfaces. For this, we start from the study and tension of the concept of information as multiplicity of multiples according to authors as Deleuze (1999), Flusser (2017), Foucault (2014) and Beiguelman (2021). From this stage, we created three distinct spaces to exemplify how information is contained in these interfaces, namely: information as a journalistic construct, information as nature of the medium and in-formation as design. Concepts of ephemerality, memory and programmed obsolescence were also used through a basis of theoretical-methodological readings and studies to understand the temporalities contained in these networks. In order to point out spaces where these updates occur, we appropriated the methodology of frames (KILPP, 2011), where we removed the image from its natural flow to recombine it in new collections and cartographies in order to make these images show us more about your initial setups. For this, we collect materials posted on Estadão profile’s on Instagram and TikTok in order to analyze them in depth. By dissecting the images, we identify the elements that compose them and regroup them in new collections. Finally, we mapped the common elements in these interfaces and made notes on how information is updated through journalistic construction, design and nature senses through the layers of information that are contained in the technical images of Instagram and TikTok.
Keywords: Instagram; Stories; TikTok; Estadão; Informação; Information